Association of serum leptin levels with central arterial stiffness in coronary artery disease patients. Issue 1 (December 2016) - Tsai, Jen-Pi; Wang, Ji-Hung; Chen, Mei-Ling; Yang, Chiu-Fen; Chen, Yu-Chih; Hsu, Bang-Gee
Abstract Background Serum adipokines have roles in the development of arterial stiffness. Our aim was to investigate the relationship of leptin and the surrogate marker carotid-femoral pulse wave velocity (cfPWV) in coronary artery disease (CAD) patients. Methods Fasting blood samples were obtained from 105 CAD patients. cfPWV was measured with the SphygmoCor system. A cfPWV > 10 m/s was defined as high arterial stiffness, and ≤ 10 m/s as low arterial stiffness. Results Thirty-seven patients (35.2 %) had high arterial stiffness, and had a higher percentage of diabetes (P = 0.001), hypertension (P = 0.010), older age (P = 0.001), and higher systolic blood pressure (SBP) (P < 0.001), diastolic blood pressure (DBP) (P = 0.021), pulse pressure (P = 0.014), and serum leptin level (P = 0.002) compared to patients with low arterial stiffness. Serum leptin levels correlated with the number of angiographically documented stenotic coronary artery vessels (P < 0.001). After adjusting for factors significantly associated with arterial stiffness, multivariate logistic regression analysis showed that leptin (odds ratio = 1.026, 95 % confidence interval: 1.002–1.051, P = 0.037) was a significant independent predictor of arterial stiffness. Conclusions Increasing serum concentration of leptin correlated positively with the total number of stenotic coronary arteries, and serum leptin level may predict the development of arterial stiffness in CAD patients.